2013
DOI: 10.1002/cncr.28339
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to effective treatment of pediatric solid tumors in middle‐income countries: Can we make sense of the spectrum of nonbiologic factors that influence outcomes?

Abstract: Background Delivery of effective treatment for pediatric solid tumors poses a particular challenge to centers in middle-income countries (MIC) already vigorously addressing pediatric cancer. This study aimed to improve our understanding of barriers to effective treatment of pediatric solid tumors in MICs. Methods An ecological model centering in pediatric sarcoma and expanding to country as the environment were used as benchmark for studying delivery of solid tumor care in MICs. Data on resources was gathere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 29 publications
2
35
0
Order By: Relevance
“…To identify possible risk factors for abandonment, we considered that the type of malignancy could be a risk factor. In our cohort, a higher rate was found for retinoblastoma, compared with other solid tumors . Similarly, Vasquez et al, in 2018 in Peru, found a significant association between a higher risk of abandonment in patients with retinoblastoma .…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…To identify possible risk factors for abandonment, we considered that the type of malignancy could be a risk factor. In our cohort, a higher rate was found for retinoblastoma, compared with other solid tumors . Similarly, Vasquez et al, in 2018 in Peru, found a significant association between a higher risk of abandonment in patients with retinoblastoma .…”
Section: Discussionsupporting
confidence: 80%
“…Treatment abandonment has been addressed in Latin America, especially in patients with childhood cancer and leukemia as an important cause of treatment failure, and strategies to overcome this problem have been implemented. However, fewer studies have focused specifically on solid tumors . Therefore, the aim of this study was to describe strategies to prevent treatment abandonment in children diagnosed with solid tumors in one reference center in Brazil, and to report its prevalence and associated factors.…”
Section: Introductionmentioning
confidence: 99%
“…The development of multimodal therapy with chemotherapy, irradiation, and surgery has increased current long‐term survival rates for children with cancer to greater than 70% in state of the art treatment centers in high‐income countries . Patients in countries with limited resources typically present with high rates of locally advanced and/or metastatic disease, which influences their prognosis . Resource‐specific validation and adaptation of the state of the art treatment regimens is required in order to make advances widely generalizable.…”
Section: Discussionmentioning
confidence: 99%
“…Financial challenges are a major impediment to development of sustainable cancer treatment centers in LMICs [18]. Due consideration needs to be given to generation of local funding through novel ideas and concepts that tap into local resources [19].…”
Section: Editorial Kulkarnimentioning
confidence: 99%